Desain, Pelaksanaan dan Evaluasi Pembelajaran pada Sekolah Menengah - Siti Julaeha; Muhammad Maky; Uus Ruswandi (Jurnal Dirosah Islamiyah, 2022)
New innovations in view of teaching and learning implementation, including PAI subjects have consequences for teachers to increase their roles and competencies, because the teaching and learning process and student learning outcomes are largely determined by the role of competent teachers in making and implementing the learning designs that have been made. Competent teachers will be better able to create an effective learning environment and will be better able to manage their classes, so that student learning outcomes are at an optimal level. One of the teacher's roles in the teaching and learning process is as an evaluator. In one teaching and learning process the teacher should be a good evaluator. This activity is intended to determine whether the goals that have been formulated have been achieved or not, and whether the material being taught is quite appropriate. . The design, implementation and evaluation of PAI learning at the secondary school level is carried out in collaboration with all teachers and the school community. More than that, PAI religious teachers have a more important role in fostering the morals of students through the learning process by making learning designs that are attractive and easy to understand and implement by students. Before teaching the teacher makes plans in the form of lesson plans, and in implementing learning the teacher becomes an example for students, the teacher always instills a disciplined attitude in learning, teaches respect for others and instills a sense of responsibility to study hard. The final value of all these processes is evaluation, one of which is by conducting an assessment, both on the process and on student learning outcomes. Keywords: design, implementation and evaluation of PAI learning